Suppression of interface impedance contrast in plane-parallel coatings - Kosoboutskyy, P.; Karkulovska, M. (Видавництво Львівської політехніки, 2015)
Досліджено спектральні та кутові умови для просвітлення границь за допомогою подавлення імпедансного контрасту, застосовуючи метод теоретичного і комп'ютерного аналізу функції обвідних спектрів багатопроменевої інтерференції. Дослідження проводились у резонансній області дисперсії діелектричної проникності в одинарних та бінарних плоско паралельних структурах. Одержані аналітичні співвідношення між кутом Брюстера/псевдо-Брюстера і параметрами структури. The paper focuses on the study of spectral and angular conditions for interface antireflection by means of impedance contrast suppression, applying the method of theoretical and computer analysis of the envelope functions of spectra of multibeam interference. The research is conducted in the resonance dispersion region of dielectric constant of the single and binary boundaries that form a plane-parallel structure. The analytical relations between the Brewster/Pseudo-Brewster angles and structure parameters are.
Keywords: спектри нормального та похилого відбивання; багатопроменева інтерференція; кут Брюстерата кут псевдо-Брюстера; тонкі плівки; просвітлюючий діелектричний шар; spectra of normal and oblique reflection; multi-beam interference; Brewster and pseudo Brewster angle; thin films; antireflection of dielectric layer